Dossiê "Displaying feelings and emotions in cultural settings" - Etnográfica, Revista (Etnográfica, 2023)
In the dossier on “Displaying feelings and emotions in cultural settings” we have gathered four articles that deal with culture and senses, feelings and emotions in different ways and cultural scenarios. The idea for the dossier came up in a conference with the same title held in Lisbon in 2009. The purpose of the conference was then to articulate a series of reflections around different forms of emotions displays in diverse cultural and political stages, in order to analyse its potential for the constitution of “communities of feeling”.